The combination of macleaya extract and glucose oxidase improves the growth performance, antioxidant capacity, immune function and cecal microbiota of piglets - Chen, Xing; Zhang, Fan; Li, Huirong; Liu, Jie; Jiang, Yanping; Ren, Furong; Huang, Libo; Yuan, Xuejun; Li, Yang; Yang, Weiren; Yang, Chongwu; Li, Shuang; et al. (Frontiers in Veterinary Science, 2023)
This study aims to investigate the effects of macleaya extract and glucose oxidase combination (MGO) on growth performance, antioxidant capacity, immune function, and cecal microbiota in piglets. A total of 120 healthy 28-day-old weaned piglets were randomly divided into two treatments of six replicates. Piglets were either received a basal diet or a basal diet supplemented with 250 mg/kg MGO (2 g/kg sanguinarine, 1 g/kg chelerythrine, and 1 × 106 U/kg glucose oxidase). The results showed that MGO supplementation increased average daily gain (ADG) and decreased feed:gain ratio (F/G) (p < 0.05). MGO increased serum superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activity, and immunoglobulin G (IgG) content (p < 0.05), but decreased malondialdehyde (MDA) and interleukin 1β (IL-1β) content (p < 0.05). The jejunal mRNA expression of nuclear factor erythroid 2-related factor 2 (Nrf2), glutathione peroxidase 1 (GPX1), and heme oxygenase 1 (HO-1) were increased in MGO group (p < 0.05), while that of kelch like ECH associated protein 1 (Keap1) was decreased (p < 0.05). The Firmicutes was significantly increased at phylum levels in MGO group (p < 0.05). In conclusion, 250 mg/kg MGO improved piglet growth, and regulated intestinal flora of piglets, which provided a theoretical basis for MGO as an alternative additive for antibiotics.